PENILAIAN EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER DI ALFA MART - Saputra, Gusman; I Ketut, Yadnyana (E-Jurnal Akuntansi, 2015)
This study focuses on how effectively Application of Accounting Information Systems (AIS) Computer Based on the Alfa Mart in the district. Kuta which is expected to provide an overview of the quality of the products and services provided along with advances in information systems and technolog. Variable in the assessment of the effectiveness of this research include data security, accuracy, relevance, variations reports, time, physical comfort, and quality of information. Method of observation, interviews and questionnaires used in the process of data collection and quantitative analysis techniques using a Likert scale data analysis techniques. Total score of 9974 is included in the Effective Criteria ( KE ) = 8575 < TO ? 11147.5. However, although included in the Effective Criteria ( KE ) to further improve the implementation of information systems that are better advised to further improve the prevention of damage caused by computer viruses to up- date antivirus each month.
Keywords: Alfa Mart, SIA, Effectiveness System